Ecological-faunistic analysis of the fish trematode fauna of the Lesser Gizilagach bay of the Caspian Sea - Шакаралієва, Є. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
In 2007–2012 in the Lesser Gizilagach Bay of the Caspian Sea, the author studied 436 fishes of 23 species by the method of complete helminthological autopsy and found 28 species of trematodes. Most of the detected species are the parasites of the eye lens, intestine, muscles, fins and gills; 1–2 species were observed in the other organs of fish. All found species, with the exception of two, are able to parasitize representatives of one or several families of fishes. In benthophages, parasitism on which is associated with feeding of benthic invertebrates, much more trematode species was recorded in comparison with other fishes. The accumulation in the body of predators of trematodes of swallowed fish was registered. Among all identified trematodes, 13 species are pathogens of fish, and 2 species are dangerous to humans.